Mexiletine for recurrent ventricular tachycardia in adult patients with structural heart disease and implantable cardioverter defibrillator: an EHRA systematic review . Issue 9 (19th July 2022) - Farkowski, Michal Miroslaw; Karlinski, Michal; Pytkowski, Mariusz; de Asmundis, Carlo; Lewandowski, Michal; Mugnai, Giacomo; Conte, Giulio; Marijon, Eloi; Anic, Ante; Boveda, Serge; Providencia, Rui
Abstract: The aim of the study was to systematically review evidence on the effectiveness and safety of oral mexiletine administered in monotherapy or in combination with other antiarrhythmic drugs for recurrent ventricular arrhythmia (ventricular tachycardia/ventricular fibrillation, VT/VF) in adult patients with structural heart disease (SHD) and implantable cardioverter defibrillators (ICDs). We systematically searched MEDLINE, Embase, and CENTRAL databases from inception to 27 August 2021 for prospective and retrospective studies investigating mexiletine in the target population. The main outcome was the reduction of ICD therapy. The main safety outcome was the presence of any serious adverse events (SAEs) leading to mexiletine discontinuation. Study quality was assessed using the Cochrane risk of bias tool or the Newcastle–Ottawa scale. Four studies comprising 86 mexiletine recipients were included in the review. We also obtained individual data of 50 patients from two studies. Ischaemic cardiomyopathy (ICM) was present in 86% of patients. The quality of included studies was moderate/low. A narrative review was undertaken as studies varied widely in terms of study population and treatment. Across studies, mexiletine treatment (with or without amiodarone) seemed to consistently reduce the number of ICD therapies especially in a population where catheter ablation (CA) was unsuccessful or contraindicated. In ICM patients deemed eligible for CA, mexiletine seemed to be inferior to CA. Mexiletine was discontinued in 14% of cases, mainly for gastrointestinal or neurological SAE. Mexiletine seems to be an option for the long-term treatment of recurrent VT/VF in adult patients with SHD, especially ICM, and ICD in whom CA was unsuccessful or not suitable.